Immune checkpoint inhibitors-induced thyroid dysfunction improves the prognosis of patients with lung cancer: a meta-analysis and systematic review - Dong, Yang; Li, Yuxia; Peng, Xingqiao; Fang, Wei (Frontiers in Endocrinology, 2026)
BackgroundSeveral studies have explored the impact of immune checkpoint inhibitor (ICI)–induced immune-related thyroid dysfunction on the prognosis of patients with lung cancer. However, inconsistencies remain among the results of different studies. Therefore, we conducted a meta-analysis to evaluate the impact of immune-related thyroid dysfunction on the prognosis of lung cancer, aiming to provide evidence-based support for clinical treatment.MethodsWe searched PubMed, Embase, the China National Knowledge Infrastructure (CNKI), and the Cochrane Library to identify studies on the association between immune-related thyroid dysfunction and the prognosis of patients with lung cancer. The search period spanned from the establishment of each database to November 2025. Two researchers independently performed literature screening, data extraction, and assessment of the risk of bias in the included studies. A meta-analysis was performed using RevMan 5.3 software.ResultsA total of 14 studies involving 2,252 patients with lung cancer were included. The meta-analysis showed that ICI-induced immune-related thyroid dysfunction improved the overall survival (OS) (HR = 0.47, 95% confidence interval, CI [0.39, 0.56], P < 0.00001) and progression-free survival (PFS) (HR = 0.44, 95% CI [0.38, 0.52], P < 0.00001) in patients with lung cancer. Subgroup analysis revealed that in both Asian and non-Asian populations, ICI-induced immune-related thyroid dysfunction was associated with improved OS (Asian: HR = 0.53, 95% CI [0.43, 0.66], P < 0.00001; non-Asian: HR = 0.32, 95% CI [0.22, 0.45], P < 0.00001) and PFS (Asian: HR = 0.45, 95% CI [0.38, 0.55], P < 0.00001; non-Asian: HR = 0.42, 95% CI [0.30, 0.58], P < 0.00001) in patients with lung cancer. Additionally, both ICI-induced hypothyroidism and hyperthyroidism improved OS in patients with lung cancer (hypothyroidism: HR = 0.47, 95% CI [0.33, 0.68], P < 0.00001; hyperthyroidism: HR = 0.28, 95% CI [0.15, 0.53], P < 0.00001).ConclusionsIn patients with lung cancer receiving immunotherapy, the development of thyroid dysfunction (a treatment-related adverse event) may indicate a more robust immune response to the therapy, which is associated with improved treatment outcomes. This finding provides evidence-based support for predicting the prognosis of patients with lung cancer treated with ICIs.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251267541.